Gambling with eliade: Las Vegas and the disaster of the sacred - Biles, Jeremy (Archaeus, 2011)
Though Mircea Eliade claims that the sacred is ambivalent - both holy and cursed - a close examination of his writings reveals a privileging of the right, or pure, side of the sacred and a concomitant suppression of the left, or impure, side. This paper turns to Georges Bataille’s theory of the sacred in order to return the suppressed, left sacred in Eliade. An investigation of the sacred "camouflaged" within the profane excesses of Las Vegas testifies to the full amplitude of the sacred, demonstrating that the ecstasies of Sin City are ambivalent, simultaneously exalting and exhausting.